Clinical and epidemiological characteristics of injuries caused by venomous snakes observed at the hospital for tropical diseases of Araguaína, Tocantins State, Brazil, from 1995 to 2000 - Paula Neto, J. B.; Ribeiro, R. S. P.; Luz, J. A.; Galvão, M.; Carvalho, S. M. D.; Haddad Junior, V. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Injuries caused by venomous snakes are considered a problem of public health in Brazil, and further studies for a better knowledge are very important. The aim of this work is to describe clinical and epidemiological characteristics that were observed from 1995 to 2000 in the Hospital for Tropical Diseases of Araguaína, Tocantins State, Brazil, which is a unit of health that takes care of patients suffering from tropical diseases. We studied 440 individuals and the most common characteristics observed were masculine sex, age among 15-45 years, bite in low members, and injuries caused by snakes of the Bothrops genus. The signs and symptoms more frequently observed were edema, pain, erythema, and bleeding. The most observed systemic manifestation was alteration of blood coagulation. The most frequent complications were abscess, necrosis, bacterial infection, and renal failure. The mortality rate was 3%. These data are very important for the evaluation of the problem.
Keywords: snakebite; Tocantins State; Brazil; epidemiology